PENGELOLAAN ALOKASI DANA DESA OLEH SUMBER DAYA APARATUR DESA TANJUNG KELANSAM KECAMATAN SINTANG - Mathilda Sunta E.42009032 (FISIP Universitas Tanjungpura Pontianak, 2013)
Thesis writing is intended to study and analyze Management Village Fund Allocation of aspect of planing in the Village of Tanjung Kelansam District of Sintang. The title chosen after seeing the phenomena in the field that there are some indications as office construction projects unfinished in the village, the low revenue village and low level of human resources. This research used a descriptive model of the kind of qualitative descriptive research. The research was conducted by four-step research, a preliminary research (pre-survey), plan-making research (Research Proposal), collection of secondary data and primary data then performed analysis on the same day after data collection in the field (interviews or observations), a research report (thesis). Location of the research in the village of Tanjung Kelansam. Research subjects include: Secretary of the District Sintang, Head of Administration at the office Sintang district, Village Chief of the Tanjung Kelansam, Secretary of the Tanjung Kelansam Village, Economic development staff Tanjung Kelansam, BPD Chief of the Tanjung Kelansam Village, community leaders in the village of Tanjung Kelansam. The conclusion of this research is the Village Fund Allocation Planning in the village of Tanjung Kelansam still not maximal. The constraints affecting the Village Fund Allocation planning is low human ability to understand the task and the lack of responsibility in the management and planning of the Village Fund Allocation Allocation Fund budget low existing village, so that the development can not proceed smoothly. Keywords: village officials, Planning, Allocation Fund Village.